Effect of turmeric extract on bone healing in an experimental model of femoral bone fracture - Shahab Ilka; Afshin Heshmati; Seyed Alireza Mirabdollahi; Abdollah Jafarzadeh; Farnaz Sedghy; Fatemeh Bagheri; Omid Azari; Mohammad Ali Mohammadi; Fatemeh Jafari Dareh Dar; Moein Arabnadvi (Mashhad University of Medical Sciences, 2022)
Objective: Following bone trauma, several factors participate in making a balance between the activity of osteoblasts and osteoclasts. The receptor activator of nuclear factor kappa B ligand (RANKL), receptor activator of nuclear factor kappa B (RANK), and osteoprotegerin (OPG) molecules play critical roles in the healing process via regulation of osteoclasts function. Turmeric is suggested to have an anti-osteogenic potential; however, its effect on accelerating bone healing has not been adequately studied. Here, we used a rat model of femur fracture to explore the effect of treatment with turmeric extract on the bone repair and the expression of RANK, RANKL, and OPG molecules.Materials and methods: Eight rats were subjected to surgery, randomly divided into two groups, and treated orally with turmeric (200 mg/kg), or olive oil. Four oil-treated rats without bone fracture were used as control group. After six weeks of treatment, the femurs of animals were examined for radiological, histological, and gene expression analysis.Results: X-ray radiography showed thicker callus and a more obscure fracture line in the turmeric group. Furthermore, higher osteoblast percentages but no osteoclasts were observed in turmeric-treated animals, representing better repair of bone in the fracture site. Also, real-time analyses showed that treatment with turmeric reduced RANK and RANKL expression (p <0.0001) and lowered RANKL/OPG ratio (p=0.01) in femoral bone tissue.Conclusion: Our findings indicated the turmeric ability to facilitate bone hemostasis and optimize the expression of key markers involved in the bone metabolism.